2021
DOI: 10.1097/bsd.0000000000001177
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hidden Blood Loss and its Risk Factors in Oblique Lateral Interbody Fusion Surgery

Abstract: Objective: The objective of this study was to evaluate the volume of hidden blood loss (HBL) and analyze its influential factors in single level oblique lateral interbody fusion (OLIF) surgery.Summary of Background Data: OLIF is a minimally invasive spine surgery and is increasingly used to treat lumbar degenerative disk diseases. It is generally believed that there is less bleeding during OLIF. However, HBL during the perioperative period is commonly ignored.Materials and Methods: From January 2018 to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 18 publications
2
22
2
Order By: Relevance
“…Second, paraspinal muscle tissue thickness might be related to large blood infiltration, allowing more blood to penetrate the tissue space. This finding is consistent with those of previous studies on HBL in patients undergoing oblique lateral interbody fusion surgery or cervical open-door laminoplasty ( 11 , 12 ). It might be important to evaluate the thickness of the paraspinal muscle at the target level of the patient using MRI before surgery.…”
Section: Discussionsupporting
confidence: 93%
“…Second, paraspinal muscle tissue thickness might be related to large blood infiltration, allowing more blood to penetrate the tissue space. This finding is consistent with those of previous studies on HBL in patients undergoing oblique lateral interbody fusion surgery or cervical open-door laminoplasty ( 11 , 12 ). It might be important to evaluate the thickness of the paraspinal muscle at the target level of the patient using MRI before surgery.…”
Section: Discussionsupporting
confidence: 93%
“…The amount of blood loss caused by in ltration in potential compartments or hemolysis is considerable and invisible to clinicians or surgeons [7,8]. It brings di culties to the prevention of postoperative anemia, incision healing problem and other complications caused by blood loss [9]. The hidden blood loss of ELIF is seldom reported in present studies [10], and the risk factors are not clear.…”
Section: Introductionmentioning
confidence: 82%
“…The concept of "hidden blood loss" was proposed. Due to the existence of hidden blood loss, the total blood loss could be much more than the visible blood loss seen during the operation [14,15], which may lead to postoperative complications such as anemia and poor incision healing condition [9,15]. It poses a threat to the patient's perioperative safety and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no evidence that the amount of HBL was associated with age, BMI, hypertension, diabetes, soft tissue thickness, preoperative PT and preoperative APTT in the present study. However, other studies found different results in the studies of HBL in other surgeries 10,29,32. For example, Cushner and Friedman et al32 found that patients with lower BMI had higher HBL in total hip replacement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found different results in the studies of HBL in other surgeries. 10,29,32 For example, Cushner and Friedman et al 32 found that patients with lower BMI had higher HBL in total hip replacement surgery. Jiang et al 10 found that thicker cervical soft tissue could lead to greater likelihood of TBL and HBL in cervical open-door laminoplasty.…”
Section: Discussionmentioning
confidence: 99%